Water Maceration of Black Mahlab Effectively Inhibits the Growth of Staphylococcus aureus Associated with Skin Infections - Oshi, Murtada Ahmed Mohmmed (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2024)
Background: With the rising risk of antibiotic resistance, our ability to combat Staphylococcus aureus (S. aureus) in skin and soft tissue infections (SSTIs) is being compromised. Purpose: This study aimed to determine the activity of several aqueous extracts of black mahlab seeds (maceration, infusion, and decoction) against S. aureus-associated SSTIs. Methods: We employed the disc diffusion Kirby-Bauer method to evaluate the anti-staphylococcal activity of the extracts. Furthermore, we used various extract concentrations to calculate each extract's minimum inhibitory concentrations (MICs) and minimum bactericidal concentrations (MBCs) against S. aureus. Result: The results revealed enhanced anti-staphylococcal activity, with inhibition zones measuring 11.5, 22.5, and 26.5 mm at concentrations of 25, 50, and 100 mg/ml, respectively. These effects were similar to ampicillin against S. aureus and significantly higher (p  0.05) than gentamicin. The extracts showed antibacterial activity with MICs and MBCs ranging from 12.5 to 25 mg/ml. Conclusion: Overall, compared to the clinically prescribed antibiotics, ampicillin, and gentamicin, black mahlab seed extract obtained by water maceration exhibits increased anti-staphylococcal activity associated with SSTIs.